FORMULATION OF RTS FROM PINEAPPLE (ANANAS COMOSUS) AND ALOE VERA (ALOE BARBADENSIS) PULP: EVALUATION OF NUTRACEUTICAL PROFILE AND SHELF-LIFE STUDIES - Renu B. Sharma; Yogesh Kumar Awasthi; Sushreeta Roy; Shreya Deb; Priya Naithani; Deergha Gupta; Nishi Saini (Malaysian Journal of Science, 2024)
Pineapple and aloe vera are rich sources of nutraceutical compounds such as flavonoids, ascorbic acid, and phenolic compounds with antioxidant properties, making them highly appealing to both consumers and processors. Aloe vera’s beneficial qualities are attributed to its polysaccharide content. Ready-to-serve (RTS) beverages are popular non-fermented drinks that are appreciated for their flavor and therapeutic potential. This study focused on developing RTS drinks from blends of aloe vera and pineapple pulp with varying sugar content (10 °Brix, 12 °Brix, 14 °Brix, and 16 °Brix) and evaluating their physicochemical, microbiological, and sensory properties over 45 days. Storage at 9 °C resulted in a slight increase in TSS, titratable acidity, reducing sugar, and microbial load, while significant decreases were observed in total sugar, pH, phenolic content, and DPPH content. Among the formulations, the RTS beverage with 12 O Brix exhibited superior physicochemical and sensory qualities. Combining aloe vera and pineapple in RTS beverages offers not only an appealing flavor profile but also potential health benefits, making them an ideal choice for product innovation.